Determinan Tax Avoidance dari Perspektif Thin Capitalization, Transfer Pricing, dan Capital Intensity - Lestari, Sri Indah; Machdar, Nera Marinda (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study focuses on analyzing the influence of thin capitalization, transfer pricing, and capital intensity on tax avoidance practices. The three variables are placed as independent variables, while tax avoidance is positioned as the dependent variable. The study was conducted using a descriptive method through a literature review by selecting journals and articles that are relevant to the research topic. The results of the study revealed that the three factors have contributed to influencing tax avoidance efforts.